2015
DOI: 10.32734/jtk.v4i2.1471
|View full text |Cite
|
Sign up to set email alerts
|

Pengolahan Limbah Laundry Menggunakan Metode Biosand Filter Untuk Mendegradasi Fosfat

Abstract: Laundry waste dominant comes from clothes softener and detergent which is one of the environmentally inhospitable material (non-biodegraduble) soit has to be processed before dumped into the waste. The basic material that use in this research is waste laundry. The purpose of this research is to decrease phosphate and surfactant content by biosand filter method which using active carbon adsorbent with ratio of mixed waste laundry and nutrition is 100%:0, 75%:25%, and 50%:50% (in % volume) by anaerobic process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The results of this study showed that the unit operation and green technology process reduced several pollutant parameters such as BOD, COD, TSS, TDS, detergent, and total phosphate as well as affected the pollutant removal efficiency, the growth rate of rice plants, the vegetative and generative development of rice plants, the harvested products per unit area of wetlands and the detergent level translocation significantly. Generally, previous studies aimed to examine the application of conventional technology that is oriented toward the effluent in meeting and complying with the Indonesian National Standard for Environmental Quality such as in the studies of Artiyani and Firmansyah [11], Astuti and Sinaga [12], Nascimento et al [13], Zulkarnain et al [14], Wahyudianto et al [6]. However, the previous studies rarely or even completely examine the opinion of Abu-Elela et al [4] in which on the other hand, many environmental, sanitation and health risks are also associated with the use of wastewater as nonagricultural plant growing media due to the presence of toxic contaminants and microbes.…”
Section: Figure 1 Reduction Of Detergent and Other Parameters Of Laun...mentioning
confidence: 99%
“…The results of this study showed that the unit operation and green technology process reduced several pollutant parameters such as BOD, COD, TSS, TDS, detergent, and total phosphate as well as affected the pollutant removal efficiency, the growth rate of rice plants, the vegetative and generative development of rice plants, the harvested products per unit area of wetlands and the detergent level translocation significantly. Generally, previous studies aimed to examine the application of conventional technology that is oriented toward the effluent in meeting and complying with the Indonesian National Standard for Environmental Quality such as in the studies of Artiyani and Firmansyah [11], Astuti and Sinaga [12], Nascimento et al [13], Zulkarnain et al [14], Wahyudianto et al [6]. However, the previous studies rarely or even completely examine the opinion of Abu-Elela et al [4] in which on the other hand, many environmental, sanitation and health risks are also associated with the use of wastewater as nonagricultural plant growing media due to the presence of toxic contaminants and microbes.…”
Section: Figure 1 Reduction Of Detergent and Other Parameters Of Laun...mentioning
confidence: 99%
“…Proses pemisahan seperti demineralisasi, penghilangan zat warna, dan desalinasi dapat dilakukan dengan menggunakan membran nanofiltrasi. Pada sebuah penelitian menunjukkan hasil bahwa, membran terbaik adalah membran dengan massa silika 5 gram yang memiliki nilai rejeksi terbaik dengan nilai 91,33% untuk kekeruhan (Aufiyah & Damayanti, 2013).…”
Section: Limbah Industri Laundriunclassified
“…Pada kondisi aerob Linier Alkyl Sulfanote (LAS) dapat terdegradasi dengan baik, namun jika dalam keadaan anaerob penyisihan LAS masih kurang baik. Salah satu penanganan yang dapat dilakukan untuk menangani masalah pencemaran yang disebabkan oleh limbah cucian motor adalah menggunakan metode Biosand Filter (Astuti, 2015).…”
Section: Pendahuluanunclassified